2021
DOI: 10.3390/su13116261
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Practice in Times of Covid-19: A Tool to Improve Education for Sustainable Development in Pre-Service Teacher Training

Abstract: Crisis situations such as the current Covid-19 pandemic are a catalyst for change. This study stresses the need to work towards achieving quality education, and to prepare future teachers in sustainability competencies. The research questions are related to the key competencies necessary to accelerate change and to how to increase awareness and literacy of the SDGs in higher education. A quantitative methodology aimed at improving the training of future teachers who engage in reflective and critical thinking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Awareness of one's emotions, desires, thoughts, values, assumptions, and behaviors was the most pronounced interpretation given to self-awareness and intrapersonal competency (Frank and Stanszus, 2019;Valley et al, 2020;Brundiers et al, 2021;Frank, 2021;Fuertes-Camacho et al, 2021). Becoming self-aware was not limited to intellectual processes but seemed to be connected with non-cognitive processes.…”
Section: Interpretations Of Self-awareness and Intrapersonal Competen...mentioning
confidence: 99%
See 3 more Smart Citations
“…Awareness of one's emotions, desires, thoughts, values, assumptions, and behaviors was the most pronounced interpretation given to self-awareness and intrapersonal competency (Frank and Stanszus, 2019;Valley et al, 2020;Brundiers et al, 2021;Frank, 2021;Fuertes-Camacho et al, 2021). Becoming self-aware was not limited to intellectual processes but seemed to be connected with non-cognitive processes.…”
Section: Interpretations Of Self-awareness and Intrapersonal Competen...mentioning
confidence: 99%
“…In line with many others, Frank and Stanszus (2019) and Frank (2021) highlighted the importance of self-care and emotional resilience but did not connect these abilities directly to the concept of self-awareness. Miguel et al (2020), Valley et al (2020), Brundiers et al (2021), andFuertes-Camacho et al (2021) proposed awareness of one's positionality, or role in local and global community as a part of self-awareness competency. Valley et al (2020) include additionally an aspect of cultural and social awareness, which in their context relates to also understanding one's privileges and how social and cultural background affects how one acts in relation to others.…”
Section: Interpretations Of Self-awareness and Intrapersonal Competen...mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies, as well as organisations [ 22 , 23 , 24 ], have indicated the need to provide a high quality of education, being even framed in the Sustainable Development Goals (SDGs) [ 22 ] and defined as the 4th goal in the Sustainable Agenda 2030 [ 23 ]. In this sense, different goals from the Healthy People 2030 [ 24 ] and the SDGs [ 25 ] indicate an imperative to provide inclusive and equitable quality education to promote a healthy environment and life. Moreover, the U.S. Department of Health and Human Services indicated that education could prevent diverse illnesses, such as obesity or hepatitis, the pinnacle of the prevention of the 4th grade [ 26 ].…”
Section: Social and Sustainable Development Gamification And Healthmentioning
confidence: 99%